TensorFlow 2 Reinforcement Learning Cookbook Over 50 Recipes to Help You Build, Train, and Deploy Learning Agents for Real-World Applications. - Palanisamy, Praveen (Packt Publishing, Limited, 2021)
This cookbook will help you to gain a solid understanding of deep reinforcement learning (RL) algorithms with the help of concise, easy-to-follow implementations from scratch. You'll learn how to implement these algorithms with minimal code and develop AI applications to solve real-world and business problems using RL.